Late Wisconsinan Morphosedimentary Sequences of the Lower Coppermine River Valley, Nunavut and Northwest Territories - St-Onge, Denis (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2012)
SUMMARY A series of late Wisconsinan sedimentary sequences occupy parts of the Coppermine River valley, and are grouped into five morphosedimentary zones representing four environments at the time of last ice retreat: glacial, paraglacial, lacustrine and marine. The sequences commonly interfinger, and document episodic deposition in time-transgressive environments related to ice frontal positions. Glacial and paraglacial sediments are, in part, reworked in a glaciolacustrine environment extending from delta topsets of bouldery gravel to bottomset rhythmites of silt-clay. The glacial-lake rhythmites formed the matrix of a later sequence of debris-flow events, which emplaced a wedge of massive diamicton in the postglacial marine sediments. This sedimentary sequence, composed of a chaotic mass of heterogeneous material that is intimately mixed, and is accumulated in the form of a semi-fluid body in a marine environment, is possibly the best exposed Quaternary olistostrome. A general overview of the Quaternary history of the area east of Great Bear Lake and north of Point Lake shows: a) deglaciation proceeded by large-scale downwasting with no discernable readvance pulses, b) that the Coppermine River valley between Point Lake and Rocky Defile Rapids was ice-free by 10 250 14C years BP, and, c) that earth-shaping processes were intensely active for a short period at the time of deglaciation; since then the landscape has been mostly quiescent.